The effect of ammonium chloride usage on the recycling of fiberboards in the hydrothermal hydrolysis method - Çağrı Olgun (Turkish Journal of Forestry)
Fiberboards, when disposed of at the end of their service life, cause some significant environmental issues such as air pollution. The recycling of fiberboards is the most effective solution to these problems; however, it has not yet found a widespread application. In the literature, there are various recycling methods for wood-based panels, but one of the most researched is the hydrothermal hydrolysis method. In this study, the effect of ammonium chloride solutions with different concentrations (0%, 2.5%, 5%, 7.5%, 10%, 15%, 20%, and 25%) on the fibers obtained through the recycling process using the hydrothermal hydrolysis method was investigated. Elemental analysis (C%, H%, N%), FT-IR analysis, SEM (scanning electron microscope) and SEM EDS (energy dispersive spectrometry) analyses were conducted to determine the properties of the recovered fibers. According to the obtained results, it has been observed that the increase in the amount of ammonium chloride significantly reduces the total nitrogen (N) content in the structure of the fiber board from 4.198% to 0.268%. Nevertheless, it has been observed that there are distortions in the morphologies of the fibers obtained with the increase in the amount of ammonium chloride. In the SEM EDS analysis results, it was found that there was no nitrogen element on the surface of the fibers recovered by treatment with ammonium chloride solution at concentrations of 20% and 25%, and when all results were evaluated, these two solutions were determined to be the optimum processing concentrations.